Academic Leaders Shaping Work-Life Culture - Laura Bryan; Cheryl Wilson (Academic Chairpersons Conference Proceedings, 2015)
Presenters and participants will discuss emerging strategies and best practices available to chairs to support the creation of departmental cultures that are friendly and responsive to the work-life needs of faculty and staff.
Keywords: Work-Life; faculty; departmental culture; academic leadership; career flexibility